METODE PEMBELAJARAN UNTUK PENDIDIKAN DASAR PERSPEKTIF AL GHAZALI - Mahmudin, Wildan; Erik Jaenudi; Fahrurroji firman; Izzuddin Mustofa; Ateng Ruhendi (Pusat Penelitian dan Pengabdian Kepada Masyarakat (P3M) STAI, 2024)
The learning process is basically done to improve personal abilities or competencies. Learning is an active process active process and a function of the total situation that surrounds the student. Individuals who learning process will go through a learning experience and try to find meaning from the experience. to find meaning from the experience. The method of religious education according to Al-Ghazali in principle begins with memorization and understanding. Al-Ghazali argues that religious education should begin to be taught to children as early as possible. possible. Because in these years, a child has the preparation to accept religious beliefs solely by believing in them and not being required to find the evidence. Meanwhile, with regard to moral education morals, teaching must lead to the formation of noble morals. Type of research used by the author in this study is library research. (library research). In general, Al-Ghazali did not express a specific method to be applied in a teaching a particular method to be applied in teaching children in elementary school. ELEMENTARY SCHOOL / MI. However, Al-Ghazali's attention in terms of this method is more aimed at specific methods for teaching religion to children. on specific methods for teaching religion to children. The method of learning methods for the elementary level according to Imam Al-Ghazali, namely the method of habituation, task method, reward method, warning method, and reprimand method. and the method of reprimand.